2009
DOI: 10.1111/j.1502-3885.2009.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

River sections at the Byzovaya Palaeolithic site – keyholes into the late Quaternary of northern European Russia

Abstract: Heggen, H. P., Svendsen, J. I. & Mangerud, J. 2009: River sections at the Byzovaya Palaeolithic site – keyholes into the late Quaternary of northern European Russia. Boreas, 10.1111/j.1502‐3885.2009.00109.x. ISSN 0300‐9483. The geological history of northern European Russia over the past two glacial cycles is reconstructed from the stratigraphy in river bluffs along the upper reaches of the Pechora River. From a till bed near the base of the sections it is inferred that the Barents–Kara Ice Sheet covered the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Thicker units of aeolian sediments are found widely further to the east in the Pechora basin where severe periglacial conditions lasted until 12 ka (Heggen et al . ; Svendsen et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thicker units of aeolian sediments are found widely further to the east in the Pechora basin where severe periglacial conditions lasted until 12 ka (Heggen et al . ; Svendsen et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…, b, ) and Heggen et al . () suggested that a huge lake (Lake Komi, around 100−80 ka) developed synchronously in western Siberia, in the Pechora region, and the lowlands between the Gulf of Finland and the White Sea. However, such regional distribution is in conflict with results from the area west of the Timan Ridge where there is evidence of northwards fluvial drainage at that time (Kjær et al .…”
mentioning
confidence: 99%
“…There are also numerous radiocarbon dates with ages of up to 40-50 ka BP recovered from surficial Palaeolithic sites 10 and 14 in Fig. 3 Svendsen et al 2004;Heggen et al 2010). These facts in combination with the 10 subtill OSL dates, mean value 174 ka, and U/Th dates c. 200 ka at Seyda (12 in Fig.…”
Section: Alpine Glaciationmentioning
confidence: 82%
“…; Heggen et al . ). These facts in combination with the 10 subtill OSL dates, mean value 174 ka, and U/Th dates c. 200 ka at Seyda (12 in Fig.…”
Section: The Age Of the Glacial Featuresmentioning
confidence: 97%
See 1 more Smart Citation